Surgical output within the Fast Track Initiative against trachoma in Amhara region, Ethiopia - Hailemariam, Begashaw; Sata, Eshetu; Halefom, Mengesha; Deathe, Andrew R; Zerihun, Mulat; Jensen, Kimberly A; Callahan, E Kelly; Beyene, Melkamu; Adriaensen, Wim; Owiti, Philip; Senkoro, Mbazi; Zolfo, Maria; et al. (The Journal of Infection in Developing Countries, 2022)
Introduction: Trachomatous trichiasis (TT) is the advanced stage of trachoma where lashes touch the globe of the eye causing permanent damage. Without eyelid surgery, TT can lead to irreversible blindness. In 2015 the Ethiopian Ministry of Health launched the Fast Track Initiative with the aim of enhancing the provision of surgical services for TT. The aims of this study were to determine the productivity of individual surgeons during the 2017 Initiative, to compare this productivity with the Ministry’s annual target indicator of ≥ 200 surgeries, and to assess the factors associated with surgical output. Methodology: This retrospective cross-sectional study utilized programmatic data on surgical output from 140 surgeons active from January 2017 through December 2017 in the eastern half of Amhara region, Ethiopia. Data were collected from a surgery monitoring dataset, analyzed, and compared to the performance targets set by the Ministry. Results: The mean annual number of surgeries carried out per surgeon was 169 (standard deviation: 111) for a total of 23,616 surgeries. Among the 140 surgeons, 38% achieved the target set by the Ministry. Location of surgical training site and estimated surgical backlog were signficantly associated with a higher surgery output. Conclusions: An increase in surgical output was observed compared to productivity prior to the Initiative, although the average annual output during the 2017 Fast Track Initiative was lower than the Ministry’s target. Using data driven approaches to setting annual productivity goals should be considered, particularly in light of fewer remaining TT cases as a result of the successful Initiative.